Development of Integrated Science Modules with Local Wisdom to Improve Environmental Literacy at State Junior High School 46 Jakarta - Firmansyah, Bagus; Maulana, Reza Aditya (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to develop an Integrated Science module based on local wisdom to enhance environmental literacy among students at State Junior High School 46 Jakarta. The development process followed the Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Local wisdom elements integrated into the module include traditional environmental practices, local flora and fauna knowledge, and cultural values related to sustainability. The module was tested for validity, practicality, and effectiveness. Expert validation involving material, media, and education specialists confirmed the module's content and construct validity. The practicality test, conducted through teacher and student responses, indicated that the module is user-friendly and engaging. Effectiveness was measured using pretest and posttest scores to evaluate improvements in students' environmental literacy, focusing on awareness, knowledge, attitude, and action components. The results revealed a significant increase in posttest scores, indicating that students who used the module showed improved understanding and positive behavioral changes toward the environment. Additionally, the integration of local wisdom helped students relate science concepts to real-life contexts, enhancing their critical thinking and sense of responsibility toward the environment. This study concludes that the integration of local wisdom in science learning materials is an effective approach to foster environmental literacy in junior high school students.